PREPARING TEACHERS FOR INCLUSIVE EDUCATION - Natalya V. Ryabova; Olga I. Karpunina (Высшее образование в России)
The article discusses the experience in professional training of teachers to implement inclusive education accumulated at the Department of special education and medical bases of speech therapy of the Mordovian State Pedagogical Institute named after M.E. Evsevev. The authors dwell on the different levels and options for professional training, retraining and advanced training of pedagogical staff (teachers-psychologists, speech pathologists, educators) engaged in development, education, social integration of persons with disabilities. The paper also views the features of psycho-pedagogical support of students with disabilities in educational process of general and vocational education.